Strategy of managing with pain in a patient with coxarthrosis disease - Andruszkiewicz, Anna; Wróbel, Beata; Marzec, Alicja; Kocięcka, Anna (Nursing Problems / Problemy Pielęgniarstwa, 2008)
Introduction. Intensity of pain sensation in coxarthrosis disease is individual. People do not react similarly to the pain. Pain which is not endurable to one person may not be endurable to another. Many patients who suffer from chronic pain manage it in a quite good way. They worked out their own strategies of managing with pain that helps them in everyday life. Aim. The main purpose of this study is to determine the strategy of managing with pain for people who suffer from coxarthrosis disease. Material and methods. Forty adult people took part in the research: 20 women (50%) and 20 men (50%) between 30 and 87 years old. Majority of them came from towns. Research was conducted with the use of The Pain Strategies Questionnaire. Results and conclusions. Data revealed that the pain intensity has an essential influence on movement but insignificant influence on work among the subjects. The most commonly used strategy of managing with pain is praying and hoping for overcoming the suffering. The least common strategy is revaluation of pain sensation. People who live in the country are more inclined to be catastrophic than people who live in town. The stronger the pain, the more intensive the prayer. Subjects, who are not paying attention and ignoring the pain, try not to apply medicines. The fewer medicines people apply, the more intensively they ignore the pain, pay no attention or revaluate pain. There is no relation between subjective evaluation of pain influence at subjects’ activity and movement. In addition to this subjects who claimed that pain had influence at their work and mood, were more catastrophic. The more the pain influenced subjects’ mood, the less they felt they could control it.